Rational use of medicines: prescribing indicators at different levels of health care - Maria Beatriz Cardoso Ferreira; Isabela Heineck; Liziane Maahs Flores; Aline Lins Camargo; Tatiane da Silva Dal Pizzol; Iraci Lucena da Silva Torres; Alvaro Koenig; Daisson José Trevisol; Adriana Mary Mestriner Felipe de Melo; Teófilo Fernando Mazon Cardoso; Maria Tereza Ferreira Duenhas Monreal; Mônica Cristina Toffoli Kadri (Universidade de São Paulo, 2013)
This multicenter study aimed to investigate prescribing patterns of drugs at different levels of health care delivery in university-affiliated outpatient clinics located in eight cities in the South and Midwest of Brazil. All prescriptions collected were analyzed for various items, including WHO prescribing indicators. A total of 2,411 prescriptions were analyzed, and 469 drugs were identified. The number of drugs prescribed per encounter, the frequency of polypharmacy, and the percentage of encounters with at least one injection or antibiotic prescribed were higher in centers providing primary health care services, compared to those where this type of care is not provided. Most drugs (86.1%) were prescribed by generic name. In centers with primary health care services, drug availability was higher, drugs included in the National and Municipal Lists of Essential Medicines were more frequently prescribed, and patients were given more instructions. However, warnings and non-pharmacological measures were less frequently recommended. This study reveals trends in drug prescribing at different levels of health care delivery in university-affiliated outpatient clinics and indicates possible areas for improvement in prescribing practices.